2017
DOI: 10.1177/0893318917692896
|View full text |Cite
|
Sign up to set email alerts
|

To Reveal or Conceal: Using Communication Privacy Management Theory to Understand Disclosures in the Workplace

Abstract: A sample of 103 full-time employees from various organizations and industries completed an online, open-ended survey to explore and understand the decisions people make to manage their private disclosures at work. Communication privacy management theory was used to understand the management of private information. Results indicate that core and catalyst criteria motivate people to reveal/conceal at work, such as boundary maintenance based on organizational culture, relational considerations, a desire for feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 42 publications
5
67
0
1
Order By: Relevance
“…With regard to privacy, Carmon et al (2013) underscored how coworker relationships are based on the sharing of private information. Likewise, Smith and Brunner (2017) argued that disclosure among coworkers is powerful in "building feelings of friendship, community, and a sense of family at work" (p. 434). Further, these scholars argued that trust in workplace relationships and "organizational culture shapes the environment either in favor of, or against, disclosures" (p. 439).…”
Section: Disclosures In Workplace Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to privacy, Carmon et al (2013) underscored how coworker relationships are based on the sharing of private information. Likewise, Smith and Brunner (2017) argued that disclosure among coworkers is powerful in "building feelings of friendship, community, and a sense of family at work" (p. 434). Further, these scholars argued that trust in workplace relationships and "organizational culture shapes the environment either in favor of, or against, disclosures" (p. 439).…”
Section: Disclosures In Workplace Relationshipsmentioning
confidence: 99%
“…CPM has been used as a framework to understand various workplace phenomena including privacy rule decision criteria used by coworkers to selfdisclose, the implicit and explicit establishment of rules to coordinate privacy boundaries, strategies to manage privacy turbulence (Smith & Brunner, 2017), peer coworker communication, and workers' health, productivity, and organizational functioning (Ploeger-Lyons & Kelley, 2017). Additionally, researchers have examined the ways organizations, employees, and coworkers describe electronic monitoring and the privacy expectations, boundaries, and turbulence that arise from this surveillance (Allen et al, 2007); Facebook friend requests among coworkers (Frampton & Child, 2013); individual and group identity construction as a result of an organizations' withholding or obscuring information (Bean, 2017); and employees' attempts to manage health information at work (Westerman et al, 2017).…”
Section: Communication Privacy Management Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite an extensive body of literature, research on self-disclosure in the workplace has been limited to health and sexual orientation (Smith & Brunner, 2017). To our knowledge, this is the first study that explored variables associated with the disclosing of minority religious identities in the U.S. workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Age. This study responded to Smith and Brunner's (2017) call to examine the influence of age on disclosing private information and indicated that older workers were significantly more likely to disclose their minority religious identities than younger workers. Consistent with previous studies (Dougherty et al, 2011), older workers in this study scored high on the religious centrality scale, which may explain why they disclosed their minority religious identities at work more often than did younger workers.…”
Section: Significant Predictors Of Minority Religious Identity Disclomentioning
confidence: 99%